Development of International Tourism in the Context of Integration Processes - KOZHEVNIKOVA, Margarita Anatolyevna; KURBAKOVA, Svetlana Nikolaevna; ARTEMYEVA, Yulia Vyacheslavovna; PALANCHUK, Nadezhda Valeryevna; UMAROV, Murad Mukhamedovich (Journal of Environmental Management and Tourism; Vol 11 No 4 (2020): JEMT Volume XI Issue 4(44) Summer 2020, 2020)
The article is devoted to the development of approaches to international tourism development in the integration processes context. Most of the existing integration associations in the tourism market have specific organizational forms and methods of integration and international cooperation. Based on the world standards, the study of methods for determining the state of international tourism allowed the authors to develop a systematization of the integration indicators main set, affecting the functioning of the tourism market. Every model of integration in the international tourism field in the world is developed. In those countries that occupy leading positions in the tourism industry, there are high indicators of the tourism market integration, which justifies the need to develop various forms of tourism market integration.